Philosophy of Science Guidance And Counseling in Indonesia and its Implementation in Pesantren Environment - Widyarto, Wikan Galuh; Hanurawan, Fattah; Arifuddin, Alfan; Syafiq, Mohamad; Fuadi, Muhammad (Proceedings Of International Conference On Islamic Counseling Studies (ICONICS), 2024)
Philosophy of science is a branch of science encompassing everything from theories, and philosophical affirmations derived from philosophy itself. Emerging disciplines in Indonesia such as guidance and counseling have an established philosophical foundation of science. The trend regarding Islamic counseling guidance in recent decades confirms the importance of the underlying philosophy of science. Islamic guidance and counseling developed with the scientific formulation of BKI including (a) the discovery of the concept and basis of BK that breathes Islam, (b) the discovery of Islamic breathing techniques, and (c) the creation of Indonesian people who are independent in their existence as khalifatullah on Indonesian earth.  Meanwhile. The development of education in Indonesia. Islamic Counseling Guidance activities began to be implemented in Islamic boarding schools, due to the need for continuous development to answer existing problems